Che. Part two, Guerrilla [videorecording (DVD)] = Partie deux, guérilla - Guevara, Che, 1928-1967; Soderbergh, Steven, 1963-; Toro, Benicio del, 1967-; Bichir, Demián, 1963-; Grondin, Marc-André (E1 Entertainment, 2009)
After the Cuban Revolution, Ernesto 'Che' Guevara is at the height of his fame and power. Then he disappears, re-emerging incognito in Bolivia, where he organizes a small group of Cuban comrades and Bolivian recruits to start the great Latin American Revolution. The story of the Bolivian campaign is a tale of tenacity, sacrifice, idealism, and guerrilla warfare that ultimately fails, bringing Che to his death.